Novel bifunctional hybrid compounds designed to enhance the effects of opioids and antagonize the pronociceptive effects of nonopioid peptides as potent analgesics in a rat model of neuropathic pain - Piotrowska, Anna (Pain, 2021)
The purpose of our work was to determine the role of nonopioid peptides derived from opioid prohormones in sensory hypersensitivity characteristics of neuropathic pain and to propose a pharmacological approach to restore the balance of these endogenous opioid systems. Nonopioid peptides may have a pronociceptive effect and therefore contribute to less effective opioid analgesia in neuropathic pain. In our study, we used unilateral chronic constriction injury (CCI) of the sciatic nerve as a neuropathic pain model in rats. We demonstrated the pronociceptive effects of proopiomelanocortin- and proenkephalin-derived nonopioid peptides assessed by von Frey and cold plate tests, 7 to 14 days after injury. The concentration of proenkephalin-derived pronociceptive peptides was increased more robustly than that of Met-enkephalin in the ipsilateral lumbar spinal cord of CCI-exposed rats, as shown by mass spectrometry, and the pronociceptive effect of one of these peptides was blocked by an antagonist of the melanocortin 4 (MC4) receptor. The above results confirm our hypothesis regarding the possibility of creating an analgesic drug for neuropathic pain based on enhancing opioid activity and blocking the pronociceptive effect of nonopioid peptides. We designed and synthesized bifunctional hybrids composed of opioid (OP) receptor agonist and MC4 receptor antagonist (OP-linker-MC4). Moreover, we demonstrated that they have potent and long-lasting antinociceptive effects after a single administration and a delayed development of tolerance compared with morphine after repeated intrathecal administration to rats subjected to CCI. We conclude that the bifunctional hybrids OP-linker-MC4 we propose are important prototypes of drugs for use in neuropathic pain.